The Implementation of Songs in Teaching Listening in Online Learning Environment - Simanjuntak, Rutmintauli (EDUJ : English Education Journal, 2023)
Language acquisition in early childhood is crucial for a child's overall cognitive and emotional development. This paper investigates the implementation of songs in English teaching for kindergarten students in an online learning environment. With the increasing prevalence of remote learning, educators face the challenge of engaging young learners in an effective and enjoyable manner. This study aims to explore how the integration of songs can enhance the listening abilities of kindergarten students during online English lessons. The research methodology involves conducting a literature review on the benefits of incorporating songs in language education and an empirical study consisting of online lessons with a group of kindergarten students. The findings indicate that the implementation of songs positively impacts students' listening comprehension, motivation, and overall engagement in the online learning environment. The results also highlight the importance of carefully selecting age-appropriate songs that align with the learning objectives and student interests. Based on the outcomes, this paper offers recommendations for educators on effectively utilizing songs in online English teaching for kindergarten students. The integration of songs in online English teaching for kindergarten students is an effective and enjoyable method to enhance their listening skills, vocabulary acquisition, cultural awareness, and overall engagement in the learning process.